Biofunctionalization of Nano Channels by Direct In‐Pore Solid‐Phase Peptide Synthesis. Issue 67 (8th November 2018) - Brodrecht, Martin; Breitzke, Hergen; Gutmann, Torsten; Buntkowsky, Gerd
Abstract: Diatom biosilica are highly complex inorganic/organic hybrid materials. To get deeper insights on their structure at a molecular level, model systems that mimic the complex natural compounds were synthesized and characterized. A simple and efficient peptide immobilization strategy was developed, which uses a well‐ordered porous silica material as a support and commercially available Fmoc‐amino acids, similar to the known solid‐phase peptide synthesis. As an example, Fmoc‐glycine and Fmoc‐phenylalanine are immobilized on the silica support. The success of functionalization was investigated by 13 C CP MAS and 29 Si CP MAS solid‐state NMR. Thermogravimetric analysis (TGA) and elemental analysis (EA) were performed to quantify the functionalization. Changes of the specific surface area, pore volume, and pore diameters in all modification steps were studied by Brunauer–Emmett–Teller based nitrogen adsorption–desorption measurements (BET). The combination of the analytical methods provided high grafting densities of 2.1±0.2 molecules/nm 2 on the surface. Furthermore, they allowed for monitoring chemical changes on the pore surface and changes of the pore properties of the material during the different functionalization steps. This universal approach is suitable for the selective synthesis of pores with tunable surface‐peptide functionalization, with applications to the synthesis of a big variety of silica–peptide model systems, which in the future may lead to a deeper understanding of complex biological systems. Abstract : A protocol for direct solid‐phase peptide synthesis inside silica pores has been developed and its success and efficacy monitored by solid‐state NMR spectroscopy.